2019
DOI: 10.3390/ijms20040986
|View full text |Cite
|
Sign up to set email alerts
|

The Proteomic Analysis of Maize Endosperm Protein Enriched by Phos-tagtm Reveals the Phosphorylation of Brittle-2 Subunit of ADP-Glc Pyrophosphorylase in Starch Biosynthesis Process

Abstract: AGPase catalyzes a key rate-limiting step that converts ATP and Glc-1-p into ADP-glucose and diphosphate in maize starch biosynthesis. Previous studies suggest that AGPase is modulated by redox, thermal and allosteric regulation. However, the phosphorylation of AGPase is unclear in the kernel starch biosynthesis process. Phos-tagTM technology is a novel method using phos-tagTM agarose beads for separation, purification, and detection of phosphorylated proteins. Here we identified phos-tagTM agarose binding pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 48 publications
0
19
0
Order By: Relevance
“…Plant propagation and development are two important aspects that could largely determine the life cycle and economic values of different crops. The special issue studied different plants species, including an energy plant Jatropha curcas [18], a biofuel tree Pongamia [19], and three economic crops [20,21,22]. Liu et al used combined analyses of the phosphoproteomics, physiological characteristics, and ultrastructure studies to identify the responses of J. curcas seedlings under chilling, and revealed significantly changed phosphoproteins under chilling stress [18].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Plant propagation and development are two important aspects that could largely determine the life cycle and economic values of different crops. The special issue studied different plants species, including an energy plant Jatropha curcas [18], a biofuel tree Pongamia [19], and three economic crops [20,21,22]. Liu et al used combined analyses of the phosphoproteomics, physiological characteristics, and ultrastructure studies to identify the responses of J. curcas seedlings under chilling, and revealed significantly changed phosphoproteins under chilling stress [18].…”
mentioning
confidence: 99%
“…On the basis of this idea, Zhao et al conducted a phosphorproteomic analysis between two maize inbred lines showing different resistance to salt stress, and found that the enhancement of potassium and sodium transportation, carbon, and redox-related metabolism could increase the salt resistance in maize [19]. In this issue, Yu et al applied a newly developed Phos-tagTM technology to identify 21 phosphorylated peptides of AGPase [20].…”
mentioning
confidence: 99%
“…Neighboring inside the BL is an endosperm tissue called BETL, and outside is a pericarp IEP. The proteome of whole maize seeds, embryos, and endosperm has been intensively investigated in recent decades [23,25,[38][39][40][41][42][43][44]. Due to the difficulty of separating tissues from kernels, the proteome for some targeted seed parts has seldom been the focus, except for BETL, whose functions have been implied to mediate embryo-endosperm interactions and play a role in plant defense by this method [45][46][47][48] To date, no attempt has been focused on BL, and very little is known about its developmental processes, as well as the physiological and molecular roles of this tissue in kernel development.…”
Section: Discussionmentioning
confidence: 99%
“…These enzymes, each with various tissue-specific and developmental specific isoforms of starch synthases (SSs, EC 2.4.1.21), starch branching enzymes (SBEs, EC 2.4.1.18), and starch debranching enzymes (DBEs, 3.2.1.41; mainly isoamylases (ISAs)) are the major groups of enzymes involved in starch metabolism. ADP-Glc pyrophosphorylase (AGPase, EC 2.7.7.27) is the key enzyme in the first mandatory step of starch biosynthesis that produces the adenosine diphosphate glucose ADP-Glc from glucose-1-phosphate (Glc-1-P) and ATP [ 25 ]. ADP-Glc acts as a substrate to extend the α-1,4 linked glucans through SSs.…”
Section: Starch Metabolism and Phosphorylasementioning
confidence: 99%